2017
DOI: 10.1177/1932296817704444
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Compare Insulin Dosing Recommendations in Real-Life Settings

Abstract: This study provides a methodology to systematically analyze real-life data generated by insulin pumps and allowed a preliminary analysis of the performance of the PDA for insulin dosing. Further testing of the methodological approach in a broader diabetes population and prospective testing of the PDA are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…38 Initially, our goal in designing iDECIDE was to improve postprandial BG by accounting for meals, exercise, and alcohol. 22 We realized that iDECIDE could easily be extended to gather real-time data that would help us better understand behaviors at the time decisions are made. With iDECIDE as a tool to measure CTs, we are now conducting a pilot study to identify unique self-care profiles based on SMBs and CTs logged in real-time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Initially, our goal in designing iDECIDE was to improve postprandial BG by accounting for meals, exercise, and alcohol. 22 We realized that iDECIDE could easily be extended to gather real-time data that would help us better understand behaviors at the time decisions are made. With iDECIDE as a tool to measure CTs, we are now conducting a pilot study to identify unique self-care profiles based on SMBs and CTs logged in real-time.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen adult patients with T1D on insulin pump therapy were recruited to participate in the study. There were exclusion criteria for portions of study reported in Groat et al 22 that limited the recruitment to patients using an insulin pump from a specific manufacturer. After consenting, participants were administered the self-management survey in an electronic format at the clinic.…”
Section: Idecide Pilot Testingmentioning
confidence: 99%
“…Participants were part of a study which did not require a large sample size. 12 Chart reviews were used to identify adults with T1D on insulin pump therapy paired with a continuous glucose monitoring system. Participants were approached about the study during routine quarterly outpatient visits and were later contacted to set up a recruiting appointment.…”
Section: Methodsmentioning
confidence: 99%